Numerical simulation of charge accumulation and transport within cross-linked polyethylene (XLPE) subjected to high electrical stresses - Nik Ali N.H.; Mohd Ariffin A.; Ab Rahman M.S.; Zaini N.H.; Abd Rahman M.S.; Osman M.; Ab Kadir M.Z.A. (Mattingley Publishing, 2023)
Aliphatic compounds; Electric field effects; Electric insulation; Electric space charge; Electrodes; Numerical models; Poisson equation; Charge accumulation; Continuity equations; Crosslinked polyethylene; Electrical charges; High voltage cable insulation; Polymeric insulation; Schottky injection; Space charge simulations; Polyethylenes